Production of inulin by using enzymatic reactions on alternate sucrose from citrullus lanatus - Nurul Bahirah, Mohamed Yusoff (2024)
This thesis discusses the production of inulin using Citrullus Lanatus as alternate sucrose thru enzymatic reactions. The lack of efficient and sustainable methods for producing inulin, a valuable prebiotic, using enzymatic reactions on alternative sucrose sources, such as those derived from Citrullus Lanatus (watermelon), poses a significant challenge in the food industries which require studies to develop novel enzymatic approaches for inulin production. Citrullus Lanatus was used as it is one of the non-seasonal fruit in Malaysia hence it is suitable as new alternate sucrose. The characterization of invertase and alternate sucrose was done prior to production of inulin by using Fourier transform infrared spectroscopy (FTIR), High performance liquid chromatography (HPLC), and ultraviolet-visible (UV-Vis) spectroscopy. Citrullus Lanatus and invertase are indirectly related through their involvement in sucrose metabolism. As a fruit, Citrullus Lanatus contains sucrose as one of its primary sugars and invertase is an enzyme which responsible for breaking down sucrose into glucose and fructose, which can be utilized for energy or storage. Based on FTIR results showed that both invertase and alternate sucrose from Citrullus Lanatus give stretching from 1636.98 cm-1 and 1636.67 cm-1 repspectively which is C-H bond. The chromatographic profile from enzymatic reaction showed the presence of sucrose, fructose, glucose and inulin. The production of inulin proceeds by One Factor at One Time (OFAT), Fractional Factorial Design (FFD), Central Composite Design (CCD) statistical method by using Design of Expert 7.1.6. These method was used for optimisation parameters of residence time, substrate concentration, temperature, enzyme concentration and pH. Screened by FFD method which showed that three parameters (substrate concentration, enzyme concentration and temperature) were significant response to produce inulin. Temperature is most significant (p-value 0.0014) nearest to ideal p-value 0.0001 in obtained higher yield. The residence time and pH has bigger p-value with smaller F-value all these significant factors were then optimized using CCD method that evaluates maximum inulin produce is 91.336 g/L and conversion yield is 20.3%.